The Government's Intervention in Functioning the Central Bank of the State Bank from the Practices of Vietnamese Law - Vien The Giang (Jurnal Cita Hukum, 2023)
This paper aims to clarify the relationship between the organizational model of the Central Bank of Vietnam and the Government. In this model, the Government has many rights to intervene directly in the implementation of the central bank function of the State Bank of Vietnam. Such direct interventions have forced the monetary policy to run or depend on fiscal policy and have been forced to pursue the short-term goals of the Government. The State Bank of Vietnam (SBV) must still supply the Central Government Budget with an amount of money through advance payments to deal with the temporary deficit in the State Budget under the Prime Minister's decision. This made the stability (in the long –term) of monetary value and the sustainable development of the national economy of the central bank become very difficult. The State Bank regularly has to focus a lot of resources on maintaining the stability of the monetary market by resolving the market's hot spots or handling weak credit institutions by administrative interventions...under the Government's requirement that has reduced the independence of the SBV when performing the central bank function.